Modeling of Haze Image as Ill-Posed Inverse Problem & its Solution - Roy, Sangita; Sinha Chaudhuri, Sheli (International journal of modern education and computer science, 2016)
Visibility Improvement is a great challenge in early vision. Numerous methods have been experimented. As the subject is random and different significant parameters are involved to improve the vision, it becomes difficult, sometimes unsolvable. In the process original image has to be retrieved back from a degraded version of the image which is often difficult to perceive. Thus the problem becomes ill-posed Inverse Problem. This has been observed that VI (Visibility Improvement) is associated with haze and blur. This complex nature requires probability distribution, estimation, airlight calculation etc. In this paper a combination of haze and blur model has been proposed with detail discussions.